Optimized synthesis of banana peel derived porous carbon and its application in lithium sulfur batteries. (April 2019) - Xue, Mingzhe; Lu, Wanzheng; Chen, Chen; Tan, Yan; Li, Bing; Zhang, Cunman
Graphical abstract: Schematic diagram for the synthesis of porous carbon from banana peel and sulfur infusion process. Highlights: Banana peel derived porous carbons were synthesized at different conditions. Hierarchical porous carbon with ultrahigh surface area and pore volume was obtained. High content of sulfur (65 wt.%) could be accommodated. High discharge capacity of 796 mA h g −1 was maintained after 500 cycles at 0.5 C. Pore volume is the key factor to determine the electrochemical performance. Abstract: KOH activation was applied to obtain hierarchical porous carbons from banana peels. The influence of alkali/carbon ratio and activation temperature on pore feature and electrochemical performance of C/S composites was investigated. Pore volume was found to have a positive correlation with discharge capacity and cycle stability and an inverse correlation to overall impedance. Porous carbon with largest pore volume of 2.04 cm 3 g −1 obtained at alkali/carbon ratio of 3.5 and 800 °C was able to accommodate 65 wt.% sulfur. Highest discharge capacity of 796 mA h g −1 was delivered at 0.5 C and 80.5% of it was kept after 100 cycles. After 500 cycles, the composite still delivered a high discharge capacity of 615 mA h g −1, indicating superior cyclestability. Optimization on sulfur content in C/S composite was explored and 65 wt.% was found to be the best proportion. Both too low and too high sulfur content resulted in inferior electrochemical performance.